Microbial species of safety concern in milk from informal processors in Harare, Zimbabwe - Desmond Tichaona Mugadza; Siyangapi Chimuti; Nicholas Midzi; Patrick Kamau Njage (Academic Journals, 2023)
In this study, the bacteriological quality and the presence of Staphylococcus aureus, Escherichia coli O157:H7, Bacillus cereus, Salmonella species, and Pseudomonas species were studied in raw milk, cultured milk, milk handlers and packaging containers. A total of 36 samples were collected over 3 months from three different farmers. Samples were analyzed for means of counts per milliliter of milk for total bacterial count (TBC), total coliform count (TCC), total E. coli count (TEC), S. aureus, B. cereus, Salmonella spp. and Pseudomonas spp. Microbial load ranged between 0.81 and 7.6 log10 cfu/ml for various critical sampling locations. Isolates of E. coli, S. aureus and B. cereus were taken for simple polymerase chain reaction (PCR) to investigate the presence of virulent genes, rfB, sei, and cytK with amplicon sizes of 1.0 kb, 500 bp and 320 bp, respectively. The sei gene was detected in 19% of the samples and 2.8% were found to have the cytK gene. The rfB gene could not be picked in E. coli. The results show poor hygienic practices at the processors and potential risk to the consumers.